DAMPAK PERNIKAHAN DINI TERHADAP KEBERLANGSUNGAN PENDIDIKAN AGAMA ISLAM DI DESA LAU REMPAK DUSUN II LAU BINTANG KEC. STMM HILIR KAB. DELI SERDANG SUMATERA UTARA T.A 2021/2022 - Parlaungan Lubis, Nahdia Suhaila, Ramlan Padang, (Fakultas Agama Islam, 2022)
Marriage is sunatullah that generally applies to all creatures, marriage is a path chosen by Allah SWT as a way for his creatures to reproduce. In the context of carrying out the educational process between husband and wife, they must have